Empowering leadership and job satisfaction of academic staff in Palestinian universities: Implications of leader-member exchange and trust in leader - Horoub, Ibrahim; Zargar, Pouya (Frontiers in Psychology, 2022)
In the aftermath of global pandemic of COVID-19, many sectors faced severe challenges to maintain security, health (psychological, and physical), and steer through the crisis by sup-porting the society. The academic sector was disrupted and faced extreme changes during the pandemic, rendering teachers vulnerable and thus, role of leaders more crucial. Building on job demand-resources model, and social exchange theory, the current study examines the moderating effect of leader-member exchange (LMX) for increasing job satisfaction that can lead to enhanced overall wellbeing in the academic setting. Additionally, the mediating role of trust in leader is focused as a vital psychological element. Through a quantitative approach a total of 250 surveys were distributed after a pilot test. Specifically, this research gathers data from 178 (71.2% response rate) university teachers from different universities across Palestine via surveys that address the role of empowering leaders on job satisfaction among teachers. the proposed model of the re-search was analyzed using Smart-PLS and PLS-SEM technique. While the results show a significantly positive effect on job satisfaction in the presence of empowering leaders, the moderating role of LMX alongside mediating impact of trust are observed. This implies that empowering leaders are highly influential in enhancing workplace for university teachers in the post-pandemic era.